A normal β-globin allele as a modifier gene ameliorating the severity of α-thalassemia in mice - Leder, Aya (The National Academy of Sciences, 1999)
Thalassemia is a heritable human anemia caused by a variety of mutations that affect expression of the α- or the β-chain of hemoglobin. The expressivity of the phenotype is likely to be influenced by unlinked modifying genes. Indeed, by using a mouse model of α-thalassemia, we find that its phenotype is strongly influenced by the genetic background in which the α-thalassemia mutation resides [129(sv/ev)/129(sv/ev) (severe) or 129(sv/ev)/C57BL/6 (mild)]. Linkage mapping indicates that the modifying gene is very tightly linked to the β-globin locus (Lod score = 13.3). Furthermore, the severity of the phenotype correlates with the size of β-chain-containing inclusion bodies that accumulate in red blood cells and likely accelerate their destruction. The β-major globin chains encoded by the two strains differ by three amino acids, one of which is a glycine-to-cysteine substitution at position 13. The Cys-13 should be available for interchain disulfide bridging and consequent aggregation between excess β-chains. This normal polymorphic variation between murine β-globin chains could account for the modifying action of the unlinked β-globin locus. Here, the variation in severity of the phenotype would not depend on a change in the ratio between α- and β-chains but on the chemical nature of the normal β-chain, which is in excess. This work also indicates that modifying genes can be normal variants that—absent an apparent physiologic rationale—may be difficult to identify on the basis of structure alone.